PENGARUH PENYULUHAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN PENGELOLAAN SAMPAH RUMA TANGGA DI WILAYAH KERJA PUSKESMAS SUNYARAGI KOTA CIREBON - Nada Aizza Alhanifa; Yani Kamasturyani; Shella Febiana Putri (LPPM ITEKES Mahardika, 2020)
Based on data from the Cirebon City Environment Office in 2019, the volume of waste in the city of Cirebon reaches 500-600 m3 per day, and it is estimated that the yield of waste production as much as 0.7 kg per person per day. Providing health information about waste, it is only limited to the importance of disposing of waste in its place and has not been focused on information in efforts to handle and reduce waste, especially at the household level. The purpose of this study was to determine the effect of health counseling on increasing knowledge of household waste management in the Sunyaragi Public Health Center Working Area In Cirebon City. This research uses experiments method with the one group pretest-posttest design. The population is all residents of homes in the work area of Cirebon City Sunyaragi Health Center as many as 2,060 inhabited houses. The sampling technique used was proportionate stratified random sampling technique of 75 residents. The instrument used in this study was a questionnaire. The results showed there were 58 people (77.3%) who had good knowledge about household waste management after giving health education, more than before giving education, as many as 26 people (34.7%). Paired t-test results showed that the p value obtained was 0.00 and smaller than the value of a = 0.05. This result shows that Ho is rejected, which means that there is an effect of health education on increasing the knowledge of household waste management in the Work Area of the Sunyaragi Community Health Center in Cirebon. It is expected that the agency will further enhance the health promotion program and educate the public regarding the importance of managing waste at the household level.